Biotechnological improvement of ornamental plants - Darqui, Flavia Soledad; Radonic, Laura Mabel; Hopp, Horacio Esteban; Lopez Bilbao, Marisa Gisela (2018)
The discovery of commercial transgenic varieties of orange petunias sold in Europe and the United States although they had never reached the approved status, and the consequent recommendation to destroy them, was the trigger to discuss about biotechnological improvement of ornamental plants. Inside the restricted world of 26 vegetal transgenic species, according to the ISAAA’s reports (http://www.isaaa.org), there are three ornamental species: carnation, rose and the Beijing University developed petunia; all of them with the same trait, a change in their colour. On the other hand, in 2014, the whole-genome sequence of carnation appeared which was the first and until now the only one among ornamental species. In this context, we review the publications from the last five years in petunia, rose, chrysanthemum and carnation. In these papers there are detailed descriptions of modification of the cascade of genes and transcription factors involved in stress situations, in different developmental stages and their regulation through different plant hormones. This knowledge will allow breeding for better and new varieties with changes in their abiotic or biotic stress tolerance, altered growth or yield and modified product quality as colour or fragrance.